The Prognostic Value of Tumor Size, Volume and Tumor Volume Reduction Rate During Concurrent Chemoradiotherapy in Patients With Cervical Cancer - Sun, Chang; Wang, Shubin; Ye, Wenjing; Wang, RanLin; Tan, Mingyu; Zhang, Hanyi; Zhou, Jie; Li, Minglun; Wei, Lichun; Xu, Peng; Zhu, Guiquan; Lang, Jinyi; et al. (Frontiers in Oncology, 2022)
Objective The purpose of this study was to investigate the relation between prognostic and tumour parameters of cervical cancer patients, such as tumour size (TS), tumour volume (TV), and tumor volume reduction rate (TVRR) after external beam radiotherapy. Methods A total of 217 patients with advanced cervical cancer, classified as Federation of Gynecology and Obstetrics (FIGO) IIa-IVa, were enrolled in study. Pre- and mid-RT pelvic magnetic resonance imaging (MRI) were performed twice, during RT and just before brachytherapy. Results The median follow-up time was 51 months (range, 7-111 months).The 5-year overall survival (OS), progression-free survival (PFS) and local failure-free survival(LFFS) rates were 81.3%, 85.1% and 92.9% respectively. Multivariate analysis revealed that tumor parameters including FIGO stage>II(Hazard Ratio, 2.377 and 95% confidence interval [CI],1.091-5.182;P=0.029), pre-RT TV > 61.6cm3(HR,0.417 and 95% CI, 0.188-0.926; P=0.032) and mid-RT TV > 11.38cm3(HR,3.192 and 95% CI,1.094-9.316;P=0.034) were observably associated with OS. While univariate analysis showed that tumor volume reduction rate(TVRR) was dramatically associated with overall survival (HR,0.204 and 95% CI 0.033-1.282;P < 0.001) and local failure-free survival (P=0.050). Conclusions In this retrospective study, TVRR and mid radiotherapy tumor volume are independent and strong prognostic parameters for patients with local advanced cervical cancer receiving CCRT.